Green training supporting eco-innovation in three Brazilian companies: practices and levels of integration - Saturnino Neto, Angelo; Jabbour, Charbel José Chiappetta [UNESP]; Jabbour, Ana Beatriz Lopes de Sousa [UNESP] (Emerald, 2014)
Purpose – The purpose of this paper is to show results from the relationship between green/environmental training and the development of three projects of low-carbon eco-innovations in top Brazilian companies. Design/methodology/approach – This study includes three organizational projects for low-carbon eco-innovations in products (A, B and C) with the objective of reducing their impact on GHG emissions, the so-called low-carbon products. Data were collected from several sources of evidence, including in-depth interviews, document analyses and direct observations. Findings – The authors verified that the environmental training interface for mitigating climate change is relevant for the systematic development of low-carbon products in most of the cases studied. Originality/value – Low-carbon eco-innovations are a trend in the corporate world; however, there is not enough literature and practical evidence on this subject. Thus, this paper adds new evidence to the literature.
Keywords: Sustainable innovation; Brazil; Eco-innovation; Environmental training; Green human resources management; Low carbon